Frogs of the genus Paratelmatobius (Anura: Leptodactylidae) with descriptions of two new species - Pombal Jr., José P.; Haddad, Célio F. B. [UNESP] (My University, 1999)
Two new species of Paratelmatobius are described from the Atlantic Forest of Sao Paulo State, southeastern Brazil. The vocalization, tadpole, and natural history of one new species are described. Natural history observations of P. poecilogaster are reported, including the description of a specialized reproductive mode. Diagnoses, measurements, figures, color in life, and distributional data for the species of Paratelmatobius are provided.
Keywords: autecology; frog; new species; Brazil; Paratelmatobius; Paratelmatobius poecilogaster